Harriet's Halloween candy - Carlson, Nancy L. (Minneapolis : Carolrhoda Books, 1982)
Harriet learns the hard way that sharing her Halloween candy makes her feel much better than eating it all herself.
School Library Journal.
Booklist.
2.4
K-3
Keywords: Halloween -- Fiction; Sharing -- Fiction; Candy -- Fiction; Dogs -- Fiction; Halloween -- Fiction; Sharing -- Fiction; Confectionery -- Fiction; Dogs -- Fiction; Halloween -- Fiction; Integrated Ed -- Language arts -- Early elementary; Sharing -- Fiction; Candy -- Fiction; Dogs -- Fiction